A prophylactic low-dose aspirin earlier than 12 weeks until delivery should be considered to prevent preeclampsia. (December 2018) - Zhu, Jing; Huang, Rong; Zhang, Jinwen; Ye, Weiping; Zhang, Jun
Abstract: Clinical trials and meta-analyses have demonstrated that low-dose aspirin can reduce the risk of preeclampsia and fetal growth restriction in high-risk pregnant women. Current obstetric guidelines recommend that the administration of low-dose aspirin to prevent preeclampsia be initiated after 12 weeks' gestation. This starting time was chosen to minimize possible risks of maternal bleeding and fetal anomalies. However, evidence from reproductive medicine, where low-dose aspirin is commonly recommended to use before and in early pregnancy, as well as existing literature, does not support these concerns. On the other hand, defective placentation resulting in a subsequent ischemic placenta is considered as the starting point of preeclampsia. Low-dose aspirin initiated in early pregnancy can balance the levels of thromboxane A2 and prostacyclin and maintain adequate uteroplacental blood flow and, therefore, improve placentation. Thus, an initiation of low-dose aspirin earlier than 12 weeks can be considered. Meanwhile, evidence shows that low-dose aspirin can improve maternal vascular endothelial function without increasing the risks of adverse maternal and perinatal outcomes. Therefore, it appears safe to use low-dose aspirin as a prophylactic until delivery.